Проблема выбора лекарственной формы материала для временной обтурации корневых каналов (Эндодонтия Today)
Practising stomatologists often enough should face treatment of destructive forms of a periodontitis, сases of endotoxic activity in teeth with necrotic pulps. In given article the reasons of occurrence of inflammatory processes in periapical tissues are surveyed. Necessity of disinfection of the infected root system speaks; the choice of the medicinal form of a material for a time obturation of root channels is carried out. It is proved that in the majority of clinical cases inflammatory processes in periapical tissues grow out of insufficient disinfection of system of root channels at primary endodontic treatment or presence necrotic pulp. This article tells about the research devoted to definition of antibacterial efficiency of application Calcium Hydroxide and Chlorhexidine, included in gutta-percha pegs, in comparison with use Calcium Hydroxide and Chlorhexidine, in the form of suspension and gel accordingly. The review of researches of foreign colleagues and results of own clinical cases allow to conclude with confidence that the gutta-percha pegs containing Calcium Hydroxide and Chlorhexidine, aren't alternative to classical provisional bandages.